Diagnostic Yield of Serial Pancreatic Juice Aspiration Cytologic Examination With Brush Cytology for Pancreatic Ductal Stenosis. Issue 8 (September 2022) - Mie, Takafumi; Sasaki, Takashi; Takeda, Tsuyoshi; Okamoto, Takeshi; Mori, Chinatsu; Furukawa, Takaaki; Yamada, Yuto; Kasuga, Akiyoshi; Matsuyama, Masato; Ozaka, Masato; Sasahira, Naoki
Abstract : Objectives: Serial pancreatic-juice aspiration cytologic examination (SPACE) is useful for diagnosis of pancreatic ductal stenosis. This study investigates the utility of adding brush cytology to SPACE during the same procedure. Methods: We retrospectively analyzed consecutive patients who underwent SPACE with brush cytology for pancreatic ductal stenosis between February 2014 and July 2020 in our hospital. Results: Thirty-four patients were included. Eleven had lesions in the pancreatic head lesions, and 23 had lesions in the pancreatic body or tail. Malignancies were found in 22 patients. Endoscopic ultrasound, computed tomography, and magnetic resonance imaging showed distal pancreatic duct dilation in 81.8% to 90.6% of cases, with a sensitivity of 63.0% to 65.5%. The sensitivity and diagnostic accuracy of SPACE, brush cytology, and SPACE with brush cytology were 63.6%, 50.0%, and 77.3% ( P = 0.19) and 73.5%, 67.6%, and 82.4% ( P = 0.42), respectively. No significant differences in diagnostic yield were observed for either pancreatic head lesions or pancreatic body/tail lesions. Post–endoscopic retrograde cholangiopancreatography pancreatitis was observed in 4 cases (11.8%). Conclusions: The utility of adding brush cytology to SPACE was limited.